Armenia Country Gender Assessment, 2016 : The State of Gender Equality in Armenia - World Bank (World Bank, Washington, DC, 2017)
Despite economic progress over the last decade, disparities between women and men remain salient in Armenia, especially in dimensions that are powerfully influenced by social norms. In domains like education and health, gender equality in outcomes in Armenia are broadly comparable with those in Europe and Central Asia and better than those of lower-middle-income countries globally. However, barriers to women's access to economic opportunities persist and gender inequalities are manifest in demographic imbalances, and under-representation in leadership roles. Concerted policy efforts are required to close gender gaps that hamper growth of the overall economy.